Healthy living in pregnancy: a cluster-randomized controlled trial to prevent excessive gestational weight gain - rationale and design of the GeliS study - Rauh, Kathrin (BioMed Central, 2014)
BACKGROUND: Recent studies suggest that excessive gestational weight gain (GWG) leads to adverse maternal and fetal outcomes including weight retention in the mother and an increased risk of childhood obesity in the offspring. The aim of the GeliS study is to examine the effect of a lifestyle intervention programme during pregnancy to avoid excessive GWG and, hence, to reduce pregnancy and obstetric complications as well as the risk of maternal and offspring obesity. METHODS AND DESIGN: The GeliS study is a multicentre cluster-randomized controlled trial. A total number of 2500 pregnant women (singleton pregnancy) with a pre-pregnancy BMI ≥ 18.5 kg/m(2) and ≤ 40 kg/m(2) will be recruited in practices of gynaecologists and midwives in ten Bavarian regions. The intervention comprises three structured and individualised counselling sessions on a healthy diet, regular physical activity as well as weight monitoring during pregnancy and one session after delivery, respectively. The counselling sessions are attached to routine pre- and postnatal visits using standardised materials and procedures. In the control regions, general recommendations for a healthy lifestyle are given. An oral glucose tolerance test is offered to all participants. The primary outcome is the proportion of participants with excessive GWG. Secondary outcomes include pregnancy and obstetric complications such as frequency of gestational diabetes, preeclampsia and caesarean sections as well as weight retention in the mothers and BMI and other health variables in the offspring. A 5-year follow-up of both mothers and their infants is planned. DISCUSSION: The GeliS lifestyle intervention programme has been adapted to the existing routine health care system for pregnant women. If shown to be effective, it could be immediately implemented in routine care. TRIAL REGISTRATION: The study protocol is registered at the ClinicalTrials.gov Protocol Registration System (NCT01958307).